THE CONCEPT OF FRACTIONS AND THE REAL APPROACH TO STUDYING MATHEMATICS (American Journal of Pedagogical and Educational Research, 2024)
Fractions are a fundamental concept in mathematics that often poses challenges for students. Traditional approaches to teaching and learning fractions have been found to be ineffective in developing a deep understanding of this concept. In recent years, the Real approach to studying mathematics has emerged as a promising alternative. This article explores the concept of fractions and examines the benefits of the Real approach in promoting a conceptual understanding of fractions among students. The Real approach emphasizes the use of real-world contexts, problem-solving, and meaningful mathematical experiences to enhance students' comprehension and application of fraction concepts.